Eficiência na fixação biológica de N2 por estirpes de Bradyrhizobium na soja em solos de Roraima - França Junior, Izaias (2012)
The objective of this work was to evaluate and select Bradyrhizobium strains that promoted nodulation in soybean crop on Cerrado soils of Roraima, Brazil. The soil collection was made in three areas of cerrado for isolation, purification and characterization of the isolates in April 2009. These isolates were evaluated for the ability to promoting nodulation in soybean under greenhouse conditions, and the best ones were selected by the symbiotic efficiency. After the efficiency tests, it were selected two strains to be tested in two soybean cultivars (BRS tracajá and the transgenic BRS 333-RR) under field conditions. After the purification and isolation procedure, were made a set of 250 bacteria, all of them with the ability to promote soybean nodulation, and 40 of them showed a good performance on nodules formation (40 per plant) and nodules dry mass. The isolates were divided in two groups, the ones with values under 0,56 g/plant, and the ones with values above 0,59 g/plant, the dry mass of the aerial part had the same response. The selected isolates were the ERR-94 and ERR-148, these were tested on the BRS-333 and BRS-tracajá cultivars, showing better performance than the usual strain for soybean. The combination of ERR-94 and BRS-333 surpassed the nitrogen treatment, showing a 149% on nitrogen biologic fixation. These results were similar to the field results. It can be concluded that the native isolates from Cerrado soils were capable to nodulating the soybean, the ERR-94 and ERR-148 strains promoted good nodulation, better nitrogen accumulation on aerial part and efficient nitrogen biological fixation. The cultivars responded positively to the inoculation with the ERR-94 and ERR-148 strains, the better combination were the BRS-333 cultivar with the ERR-94 strain.